Possibilities to Detect Greenwashing and to Prevent Confusion - Dangaasuren, Odmaa; Sukhbat, Davaakhishig (Mongolian Journal of Economic Review, 2025)
The significance of interactions between humans and nature has been recognized globally since the mid-1990s. Following this trend, businesses and individuals have shown a preference for products that are ecologically friendly and recyclable. According to the report “Consumers Would Partner with Brands for Social Change, Environment” (2007, International Marketing Charts), companies have increasingly utilized greenwashing technologies to capitalize on the growing consumer demand for environmentally friendly products. The overuse of greenwashing technology has had a substantial influence on human life, health, and the environment in recent years; hence, this topic was chosen for investigation. This article examines incidents of "greenwashing" technology in the food sector on a global scale, using the Coca-cola Company as an example, to assess how it satisfies greenwashing standards. Ногоон угаалгыг илрүүлэх, төөрөгдөлтөөс сэргийлэх боломж Хураангуй: 1990-ээд оны дунд үеэс дэлхий нийтээрээ хүн, байгалийн дасан зохилдлого чухал болохыг ойлгож эхэлсэн билээ. Тухайн чиг хандлагыг дагаж байгууллага, хэрэглэгчид харилцан байгальд ээлтэйгээр үйлдвэрлэгдсэн, дахин боловсруулагдах боломжтой хэрэглээг эрхэмлэх болов. “Consumers Would Partner with Brands for Social Change, Environment” (2007, International Marketing Charts)-ийн тайланд дурдсанаар байгаль орчинд ээлтэй бүтээгдэхүүний өсөн нэмэгдэж буй хэрэглэгчдийн эрэлт хэрэгцээг ашиглан компаниуд ногоон угаалгын (greenwashing) технологийг түгээмэл ашигладаг болсон гэжээ. Ногоон угаалгын технологийг хэтрүүлэн ашиглах нь сүүлийн жилүүдэд хүний амь нас, эрүүл мэнд, байгаль орчинд хүчтэй нөлөө үзүүлж эхэлсэн тул энэхүү сэдвийг сонгон судалсан болно. Уг өгүүлэлд олон улсын хэмжээнд хүнсний бүтээгдэхүүн үйлдвэрлэлийн салбарт “ногоон угаалга”-ын технологийг ашигласан тухай Coca-Cola компанийн жишээн дээр кейсүүдийг шинжилж, ногоон угаалгын норматив хэм хэмжээг хангаж буй эсэхийг судалсан болно. Түлхүүр үгс: Ногоон PR, хүрээлэн буй орчин, хүний эрүүл мэнд, нийгмийн хариуцлага, норматив хэм хэмжээ Author name correction: Damgaasuren was changed to Dangaasuren